Pengaruh Gratis Ongkos Kirim (Ongkir), Discount, dan Collect On Delivery (Cod) terhadap Keputusan Pembelian di Tiktok Shop (Studi Kasus Pengguna Tiktok Shop pada Mahasiswa Fakultas Ekonomi Universitas Methodis Indonesia - Purba, Hanna Rumeni; Nadapdap, Kristanty Marina Natalia; Saragih, Rintan Br (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This study aims to analyze the effect of free shipping (postage), discounts, and Collect on Delivery (COD) on purchase decisions at TikTok Shop in students of the Faculty of Economics, Methodist University of Indonesia (UMI). The background of this research is based on the rapid development of e-commerce, especially TikTok Shop, which attracts the attention of young consumers such as students. COD payment methods and promotions such as free shipping and discounts are the main attractions of TikTok Shop in influencing purchase decisions.This study uses a quantitative method by involving students of the Faculty of Economics UMI as respondents. Data collection was carried out through a questionnaire with a Likert scale to measure students' perception of the influence of free shipping, discounts, and COD on their purchasing decisions. The collected data was analyzed using descriptive and inferential statistical methods to test the research hypothesis using IBM SPSS version 25. The results of the study explained that the Free Shipping variable partially had a positive and significant effect on Purchase Decisions. This variable explains that the Discount Payment variable partially has a positive and significant effect on the Purchase Decision. This variable explains that the Cash On Delivery (COD) Payment variable partially has a positive and insignificant effect on Purchase Decisions.